Industrial Development Report 2024 - United Nations Industrial Development Organization (United Nations, 2024)
The Industrial Development Report 2024 (IDR24) emphasizes the pivotal role the industrial sector plays in delivering sustainable development solutions, given its profound impact on economic, societal and environmental goals. Sustainable industrialization entails fighting climate change, promoting economic growth and generating millions of decent jobs while harnessing cutting-edge technologies. The report finds that every manufacturing job, on average, creates more than two jobs in other sectors of the economy. The manufacturing sector also significantly contributes to green innovation compared to other sectors, with 60 per cent of all green patents worldwide owned by industrial firms, despite representing a smaller share of the overall firm population. Accelerating sustainable industrial development is therefore crucial for achieving the Sustainable Development Goals (SDGs).